PERTUMBUHAN BIBIT KELAPA SAWIT PRE NURSERY DENGAN MODIFIKASI NUTRISI DAN BERBAGAI MACAM MEDIA TUMBUH PADA SISTEM HIDROPONIK - Yohana Theresia Maria Astuti; Retni Mardu Hartati; Tejo Triwaluyo (Program Studi Agroteknologi INSTIPER, 2019)
The aimed of this study was to determine the growth of oil palm seedlings at pre nursery in the nutrition modification and various types of media on hydroponic systems. The research was conducted at the education and research garden of the Stiper Agricultural Institute Yogyakarta, Maguwoharjo Village, Depok District, Sleman Regency, Yogyakarta Special Region in March to June 2016. The study used a split plot design. Main plot is a modification of nutrition consisting of three levels, namely nutrition A (15 g gandasil, 15 g hyponex, 0.78 g ZA, 7.5 g dolomite), nutrition B (15 g gandasil, 15 g hyponex, 1.17 g ZA, 11.25 g dolomite), and nutrition C (15 g gandasil, 15 g hyponex, 1.56 g ZA, 15 g dolomite). While the sub plot is a planting medium consisting of three types, namely rockwool, husk charcoal, and cocopeat. Observation data were analyzed by variance. To find out the significan difference between treatments is done by Duncan Multiple Range Test (DMRT) at a 5% significan level. The results of the analysis showed that nutrient modification had an effect on the number of leaves and leaf area, nutrients B and C were better than nutrition A, however, nutrition A, nutrition B, and nutrition C had the same effect on the growth of pre-nursery of oil palm with hydroponic systems. Various types of planting media influence the growth of pre-nursery oil palm seedlings, best on rockwool media. Keyword : oil palm, hydroponic, nutrition modification, planting media.